STRATEGI DAN MEDIA PEMBELAJARAN DALAM IMPLEMENTASI PENDEKATAN DEEP LEARNING - Irfan Masrur; Naily Inayatul Maghfirah (Jurnal Al-Fatih, 2025)
The Ministry of Education and Culture recently launched a new approach to teaching and learning activities, namely the Deep Learning Approach. Mindful, Meaningful, and Joyful are the three main principles in the Deep Learning approach. This study aims to analyze various learning strategies and media relevant to the implementation of the Deep Learning approach in educational environments. The type of research used is library research, namely research conducted by reviewing various literature sources such as books, scientific journal articles, proceedings, and previous research results related to strategies, learning media, and the application of Deep Learning. Data were collected through document studies of relevant literature sources, then analyzed using content analysis methods to identify concepts, patterns, and relationships between strategies and learning media in supporting Deep Learning. The results of the study indicate that the implementation of Deep Learning requires learning strategies that are student-centered, collaborative, reflective, and problem-solving based, such as project-based learning, problem-based learning, inquiry learning, collaborative learning, and flipped classroom. Meanwhile, effective learning media to support this approach include interactive digital media, online learning platforms, and visual and audiovisual-based media that can stimulate students' cognitive and affective engagement. The conclusion of this study confirms that the successful implementation of Deep Learning depends heavily on the selection of appropriate, contextual learning strategies and media that encourage students to think critically, creatively, and independently.